Analysis of Inventory Behaviour -An Application Model for Selected Indian Cement Companies - Hamsalakshmi, R.; Sekar, M. (Gyan Management Journal, 2007)
It is action time now for the Indian cement industry, which was plagued by fragmentation and overcapacity. A booming infrastructure sector coupled with a vibrant housing sector has injected a new lease of life into the sector, which had almost become moribund just a couple of years ago. However, as a result of consolidation over the last five years, the players have not only been able to achleve economies of scale but also have improved their efficiency. Indeed a spate of big-ticket acquisitions and greater capacity utilization have brought aoout the much needed zing in the rather insipid industry. The cement industry contributes 1.3% to the GDP and employs over 1.4 lakh people. It is a significant contributor to the state coffers in terms of excise and sales taxes since the tax buoyancy of cement is very high. In India, both installed capacity and actual production have grown significantly over the past few decades. According to India's leading rating agency ICRA, on a decadal basis cement production in the country increased at an annual average of 8.2%
Keywords: Inventory Behaviour; Application Model; Indian Cement Companies